Palaeotropical origins, boreotropical distribution and increased rates of diversification in a clade of edible ectomycorrhizal mushrooms (Amanita section Caesareae). (27th August 2014) - Sánchez‐Ramírez, Santiago; Tulloss, Rodham E.; Amalfi, Mario; Moncalvo, Jean‐Marc; Carine, Mark
Abstract Aim The geographical distributions of most fungal species are still poorly known; consequently, their origins and historical distributions remain largely understudied. High levels of cryptic diversity, scarce fossil records and poorly sampled regions can explain some of these shortcomings. We extensively sampled an iconic group of edible ectomycorrhizal (EM) fungi, Amanita caesarea and its allies, in order to infer evolutionary patterns on a global scale. Location Worldwide. Methods DNA sequences from three nuclear genes were derived for 120 collections. Divergence times were estimated using fossil calibrations within the Agaricomycetes, followed by more inclusive (A. sect. Caesareae + outgroup) root‐recalibrated estimations. Ultrametric trees from beast were used in ancestral‐area reconstructions and to infer geodispersal models. They were further used in diversification‐rate analyses using maximum‐likelihood and Bayesian methods. Results Molecular dating and ancestral‐area reconstruction indicated a Palaeotropical origin of A. sect. Caesareae between the Palaeocene and Eocene. Dispersal events to temperate regions in Mediterranean Europe, eastern Australia and North and Central America, occurred mostly during the late Miocene and Pliocene. A boreotropical model was supported as the most likely mode of geodispersal. Diversification rates were significantly higher in the New World than in the Old World. Main conclusions We present evidence that this group of edible EM mushrooms was ancestrally Palaeotropical from around the Eocene to the late Miocene, reaching temperate insular and continental areas during the late Miocene and Pliocene. The mode of dispersal is largely consistent with Wolfe's boreotropical hypothesis. We also found that the overall diversification rate has been rather constant, but has increased relatively recently in the New World, possibly as a result of the well‐documented Plio‐Pleistocene climatic fluctuations.